2009
DOI: 10.1002/lapl.200910054
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond four-wave mixing spectroscopy on CdS crystal at room temperature

Abstract: Abstract:The results of the femtosecond four-wave mixing measurements performed on the CdS crystal at room temperature are reported. The dephasing time T d = 180 fs was obtained. The anti-Stokes shift of the primary photon echo spectrum with respect to the excitation spectrum was observed. The some peculiarities of the coherent responses decay curves indicate that this optical dephasing is due to the exciton-exciton interaction. The stimulated photon echo decay curves appear to have a fast decay component (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…3. The decay time was found to be equal to 170 -180 fs that is close to the optical dephasing time at room temperature [7].…”
Section: Experimental Observation Of Efid Signal In Cds Semiconductormentioning
confidence: 51%
“…3. The decay time was found to be equal to 170 -180 fs that is close to the optical dephasing time at room temperature [7].…”
Section: Experimental Observation Of Efid Signal In Cds Semiconductormentioning
confidence: 51%
“…Let us now consider the physics of FCPE signals formation in the CdS crystal. It is based on the two-photon character of absorption of the 793 nm femtosecond Ti:sapphire laser radiation that was experimentally shown earlier by other authors in [4,5] and also in our work [6]. The excitation is carried out simultaneously by two laser beams crossed (in the same region of CdS film) at an angle of 60° propagating in the directions of wave vectors k 1 and k 2 .…”
Section: Femtosecond Correlated Photon Echo Signalsmentioning
confidence: 58%
“…The experiment was performed using degenerate fourwave mixing (DFWM) technique in CdS crystal in a temperature range from 5 to 300 K [4]. We also carried out a similar experiment in 2009 [6]. A scheme of the femtosecond photon echo excitation and detection in this mode is shown in figure 2.…”
Section: Femtosecond Correlated Photon Echo Signalsmentioning
confidence: 99%
“…Earlier, in [12], it was shown that the two-photon regime is necessary for the resonant excitation of the CdS crystal by 800 nm laser radiation of the Ti:sapphire laser. Then, following [7], we experimentally show that in the case of CdS nanopowder one needs the three-photon regime of excitation [13]. In the experiment study in [3] it was shown that the semiconductor nanoparticles CdSe-CdS, known as nanostructures of 'core-shell' type, can play the role of such a nanopowder.…”
Section: Peculiarities Of the Ensemble Of Cdse-cds Quantum Dotsmentioning
confidence: 92%